Exploring gaps and opportunities in primary care following an asthma hospital admission: a multisite mixed-methods study of three data sources. Issue 5 (4th January 2023) - Jones, Renee; Hiscock, Harriet; Shanthikumar, Shivanthan; Lei, Shaoke; Sanci, Lena; Chen, Katherine
Abstract : Objective: Explore gaps and opportunities in primary care for children following a hospital admission for asthma. Design: Exploratory mixed-methods, using linked hospital and primary care administration data. Setting: Eligible children, aged 3–18 years, admitted to one of three hospitals in Victoria, Australia between 2017 and 2018 with a clinical diagnosis of asthma. Results: 767 caregivers of eligible children participated, 39 caregivers completed a semistructured interview and 277 general practitioners (GPs) caring for 360 children completed a survey. Over 90% (n=706) of caregivers reported their child had a regular GP. However, few (14.1%, n=108) attended a GP in the 24 hours prior to index admission or in the 7 days after (35.8%, n=275). Children readmitted for asthma (34.2%, n=263), compared with those not readmitted (65.8%, n=504), were less likely to have visited a GP in the non-acute phase of their asthma in the 12 months after index admission (22.1% vs 42.1%, respectively), and their GP was more likely to report not knowing the child had an asthma admission (52.8% vs 39.2%, respectively). Fewer GPs reported being extremely confident managing children with poorly controlled asthma (11.9%, n=43) or post-discharge (16.7%, n=60), compared with children with well-controlled asthma (36.4%, n=131), with no difference by child readmission status. Conclusions: Given the exploratory design and descriptive approach, it is unknown if the differences by child readmission status have any causal relationship with readmission. Nonetheless, improving preventative patterns of primary care visits, timely communication between hospitals and primary care providers, and guideline concordant care by GPs are needed.